The impact of multidisciplinary accompaniment interventions on negative emotions and caregiving ability of family members of ostomy patients: exploring the mediating effect of social isolation - Yu Liu; Xuemei Li; Li Wang (Frontiers in Psychology)
BackgroundAlmost half of stoma caregivers develop anxiety or depression, yet follow-up still centers on patients and offers caregivers little structured support. Social isolation—worsened by the pandemic and likely to grow as colorectal-cancer ostomies rise—appears central to this distress, but its role in caregiver programs has never been tested. We therefore assessed a 12-week multidisciplinary accompaniment program and measured how much reducing isolation improves caregivers' skills and emotional wellbeing.MethodologyA cross-sectional study was conducted with 302 family caregivers of ostomy patients. Participants were divided into an Intervention Group (IG) and a Non-Intervention Group (NIG). Logistic regression models examined associations between demographic and behavioral factors, caregiving outcomes, and social isolation. Mediation analysis was performed to determine the indirect effects of social isolation on caregiving ability and negative emotions.ResultsMultidisciplinary accompaniment interventions significantly improved caregiving ability (OR = 2.33, 95% CI: 1.12–3.54), reduced negative emotions (OR = 2.58, 95% CI: 1.13–4.03) and social isolation score (OR = 1.69, 95% CI: 1.09–2.29), with social isolation accounting for 18.7% of the effect on caregiving ability and 15.2% on negative emotions. In addition, significant predictors also included place of residence, marital status, and alcohol consumption.ConclusionsMultidisciplinary accompaniment interventions that address social isolation can enhance caregiving ability and reduce emotional strain in family caregivers of ostomy patients.